2021
DOI: 10.1016/j.ibusrev.2021.101856
|View full text |Cite
|
Sign up to set email alerts
|

The impact of international diversification on credit scores: Evidence from the UK

Abstract: Despite the great deal of previous research into international diversification, we know little about the impact of international diversification on firms' credit scores. Drawing upon the resource-based view and transaction cost economics, we examine the relationship between international diversification and credit scores by using a large sample of 6,557 UK firms between 2016 and 2017. We find an inverted U-shaped relationship between international diversification and firms' credit scores, indicating that firm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 128 publications
0
0
0
Order By: Relevance
“…Regarding the impact of firm size on diversification (SIZE), some authors consider larger firms often achieve greater diversification: economies of scale, economies of range, market power, learning, and experience effect. A firm's credit score is less dependent on international diversification for large firms, firms in the manufacturing sector, and firms distant from London (Halabi et al, 2021). In addition, these large firms have the means and capabilities to invest in the most efficient and sophisticated governance systems, since they have the significant resources to easily enter new markets.…”
Section: Results Of Estimates and Interpretationsmentioning
confidence: 99%
“…Regarding the impact of firm size on diversification (SIZE), some authors consider larger firms often achieve greater diversification: economies of scale, economies of range, market power, learning, and experience effect. A firm's credit score is less dependent on international diversification for large firms, firms in the manufacturing sector, and firms distant from London (Halabi et al, 2021). In addition, these large firms have the means and capabilities to invest in the most efficient and sophisticated governance systems, since they have the significant resources to easily enter new markets.…”
Section: Results Of Estimates and Interpretationsmentioning
confidence: 99%
“…Therefore, we run Equation (2) separately for exporting firms and non-exporting firms. Firms with foreign sales are categorized as exporting firms, while those without foreign sales are considered nonexporting firms (Halabi et al, 2021). The findings in columns 5 and 6 of Table 6 show that the interaction term between πΌπ‘šπ‘π‘Žπ‘–π‘Ÿπ‘šπ‘’π‘›π‘‘ !"…”
Section: The Impact Of Firm-level Information Environmentmentioning
confidence: 99%
“…The new measure was calculated as goodwill at the end of the year plus goodwill impairment in the year minus goodwill at the beginning of the year. The results are essentially unchanged.20 Further, to control for international exposure, we repeated this analysis using a firm's level of international diversification (Int-Div), measured as a percentage of foreign sales to total sales (seeHalabi et al, 2021). In untabulated results, we found that the coefficient of Weak-FTR remains positive and significant while the interaction between Weak-FTR and Int-Div is negatively significant, indicating the impact of FTR on goodwill impairments is less pronounced for internationally diversified firms.…”
mentioning
confidence: 99%